Od Girl, Woman, Other do Dekle, ženska, druga_i: spolno nevtralni jezik in literarni prevod - Zakrajšek, Katja (Hieronymus, 2025)
FROM GIRL, WOMAN, OTHER TO DEKLE, ŽENSKA, DRUGA_I: GENDER-NEUTRAL LANGUAGE AND LITERARY TRANSLATION. Linguistic expressions of gender, gender perceptions and identities change along with society; but while there is an international tendency towards developing gender-inclusive/gender neutral as well as nonbinary langu-age, both rhythms of change and grammatical possibilities differ from language to language. Slovenian is a highly-gendered language where cur-rent best gender-neutral practices are as yet very experimental and not generally known, as well as more complex and visible than their English counterpart, the singular »they«. Still, literary translators can’t wait for these linguistic means to become generally established before engaging with contemporary texts including and exploring this aspect of language and/or texts by non-binary authors. After outlining the currently-available means and strategies for gender- -neutral language in Slovenian, including recommendations by relevant advocacy groups and organisations as well as the few linguists who have written on the subject, the paper presents the author’s own process of sha-ping the linguistic depiction of a non-binary character in the Slovenian translation of Bernardine Evaristo’s novel Girl, Woman, Other. Dilemmas and challenges are pointed out (such as the higher visibiliy of gender-ne-utral language in the translation as compared to the original due to the use of the underscore, including in the title Dekle, ženska, druga_i) and the decisions taken are discussed and contextualised.